Elderly Care, Intergenerational Relationships and Social Change in Rural China - Cao, Fang (Springer Nature Singapore : Imprint: Palgrave Macmillan, 2019)
This book investigates how rapid socio-political-economic change in China since 1949 has affected intergenerational relationships and practices in rural areas, specifically the care provided to elderly parents by their adult children. It focuses on the lived experiences of rural villagers and their perceptions of the impact of these socio-political changes on intergenerational relationships, care of the elderly, family cohesion, and the traditional value of filial piety. It notably considers the importance of filial piety as a dominant family value, the conflict between strong family bonds and growing desires for individuality and autonomy, the prevalence of migrant work among adult children and the diversification of intergenerational practices, alongside the need for national policy and services development for residential and community-based aged care in rural China.